Through a Glass, Darkly: Representation and Power in Research on Organized Abuse - Salter, Michael (Qualitative Sociology Review, 2013)
This paper draws on the author’s experience undertaking life history research with adults with histories of organized child sexual abuse. Organized abuse has been a particular flashpoint for controversy in debates over child abuse and memory, but it is also a very harmful and traumatic form of sexual violence. Research participants described how, in childhood, threats and trauma kept them silent about their abuse, but in adulthood this silence was reinforced by the invalidation that accompanied their efforts to draw attention to the harms that have befallen themselves and others. This paper will examine the role of qualitative research in addressing a form of alterity whose defining characteristic is the silencing and dismissal of narrative.